Digital Literasi Keuangan , Financial Technology Pembayaran, dan Kinerja Keuangan UMKM : Analysis Structural Equation Modeling – PLS - Swandani, Swandani (UMSurabaya Publishing, 2025)
This study aims to analyze the relationship between digital financial literacy and the use of financial technplogy payments on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). The population of this research includes MSMEs operating in Maros Regency, South Sulawesi Province. The research adopts a quantitative approach employing purposive sampling, where 32 MSME owners were surveyed through structured questionnaires, allowing the researcher to directly observe and communicate with the business owners. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with SmartPLS 4.0. to examine causal relationships among variables. The empirical results reveal that both digital financial literacy and fintech payment adoption have a positive and significant influence on MSME financial performance. Enterprises with higher levels of digital financial literacy are more capable of leveraging fintech payments platforms effectively, resulting in improved efficiency and financial performance. Furthermore, the study demonstrates that the adoption of fintech payments contributes to the improvement of financial performance among MSMEs in Maros Regency, South Sulawesi. Fintech adoption also enhances the quality and timeliness of financial reporting, which aligns with the principles of financial accounting theory. These findings emphasize are expected to provide valuable contributions to MSME development and increase awareness of the importance of digital financial literacy and utilizing fintech payment services in the digital economy era.